Influence of Hydroxytyrosol Acetate Enrichment of an Oil Rich in Omega-6 Groups on the Evolution of Its Oxidation and Oxylipin Formation When Subjected to Accelerated Storage. A Global Study by Proton Nuclear Magnetic Resonance - Sofía del Caño-Ochoa; Ainhoa Ruiz-Aracama; María D. Guillén (MDPI AG, 2022)
Sunflower oil samples, both unenriched and enriched with four different concentrations of hydroxytyrosol acetate, were subjected to accelerated storage at 70 °C until a very advanced oxidation stage and the process was monitored by 1H NMR spectroscopy. The aim of the study is to know the effect that the presence of this antioxidant has on the oxidation process of sunflower oil under the aforementioned conditions, as well as on the formation and evolution of the concentration of a significant number of oxylipins. The oxidation process was studied globally by monitoring, during storage time, the degradation of both the linoleic acyl group of sunflower oil, which is the main component of sunflower oil, and the added hydroxytyrosol acetate. Simultaneously, the identification of up to twenty-six different types of oxylipins formed in the oxidation process and the monitoring of the evolution of their concentration over the storage time were carried out. In this way, essential information about the effect that hydroxytyrosol acetate provokes on the oxidation of this oil rich in omega-6 polyunsaturated acyl groups, has been obtained. It has also been shown that the enrichment of sunflower oil with this antioxidant under the conditions tested does not prevent the oxidation process but slows it down, affecting the entire oxidation process.